A novel spreading dynamic based on adoption against the trend - Hao, Jiaqi; Ma, Jinming; Liu, Siyuan; Tian, Yang (Frontiers in Physics, 2024)
In the spreading dynamics of previous fashion trends adoption researchers have neglected to consider that some individuals may behave differently from the popular tendencies, which are called opposite trend adoption behavior. To explore the dissemination mechanisms of the behavior, we firstly establish the adoption against trend model. Additionally, an edge division theory based on the adoption of opposite trends was proposed to quantitatively analyze this unique dissemination mechanism. This study presents three various degrees of opposite trend, each highlighting unique spreading scenarios. In the case of a strong opposite trend, there will be no spreading. In the case of a weak opposite trend, limited contact will accelerate information spreading, but it will not alter the mode of spreading. Nevertheless, in the case of a moderate opposite trend, the degree of opposite trend alters the mode of spreading. Meanwhile, a crossphase transition occurs. The paper's findings can be applied to social media and commercial trades, among other areas.